Water issues in Southeast Asia present trends and future directions - Lee, Poh Onn (Institute of Southeast Asian Studies, 2013)
Provides a summary of key points made during a two-day forum on water issues in Southeast Asia, held at the Institute of Southeast Asian Studies (ISEAS), based around a UN prediction that up to 7 billion people in 60 countries may possibly face water scarcity by the year 2050.